Stres dengan Hiperemesis Gravidarum Pada Ibu Hamil - Ni Made Dewi Susanti; Ferdy Lainsamputty; Veni Ilestari (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; Hyperemesis gravidarum is excessive nausea and vomiting that occurs during pregnancy and one of the causes is stress. Stress is a psychological form that plays an important role in the symptoms of hyperemesis gravidarum. The purpose of analyzing the relationship between stress and hyperemesis gravidarum in the working area of the Community Health Center. Method; This study was an observational analytic study using a cross-sectional. The questionnaire used is the Depression Anxiety Stress Scale (DASS 42). Descriptive statistics and bivariate analysis (Mann-Whitney) were used to find the relationship between variables. Results; showed a significant relationship between stress and hyperemesis gravidarum with a p-value of 0.001 or <0.05. Conclusion; Pregnant women who experience hyperemesis gravidarum have more severe stress